2007
DOI: 10.1007/s11199-007-9343-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Attire, Alcohol, and Gender on Perceptions of Date Rape

Abstract: This investigation explored three categories of college students' perceptions of sexual assault: perceptions of similarity to vignette characters, perceptions of vignette characters' sexual intent, and victim-blaming behaviors, using a convenience sample of 652 U.S. undergraduates and an on-line factorial survey containing a two-part heterosexual date rape vignette. This investigation predicted that vignette character attire, character alcohol use, and participant gender would each significantly influence perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0
9

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(96 citation statements)
references
References 25 publications
2
85
0
9
Order By: Relevance
“…Publications on heterosexual dating in Sex Roles over the last 10 years have included articles on dating behaviors, attitudes, and outcomes among and between particular social group members (e.g., Bentley et al 2007); dating scripts, including first-date scripts, rape scripts, and hookup scripts (e.g., Morr Serewicz and Gale 2008); media influences on dating (e.g., Zurbriggen and Morgan 2006), and dating violence and coercion (e.g., Maurer and Robinson 2008).…”
Section: Dating Research In Sex Roles From 2000 To 2010mentioning
confidence: 99%
“…Publications on heterosexual dating in Sex Roles over the last 10 years have included articles on dating behaviors, attitudes, and outcomes among and between particular social group members (e.g., Bentley et al 2007); dating scripts, including first-date scripts, rape scripts, and hookup scripts (e.g., Morr Serewicz and Gale 2008); media influences on dating (e.g., Zurbriggen and Morgan 2006), and dating violence and coercion (e.g., Maurer and Robinson 2008).…”
Section: Dating Research In Sex Roles From 2000 To 2010mentioning
confidence: 99%
“…Robust predictors of culpability attributions toward sexual assault victims identified in the literature include gender, perceived similarity to a victim, empathy, and rape myth acceptance. Specifically, attribution studies consistently have shown that men attribute greater culpability to sexual assault victims than women; men also have been found to attribute less culpability to perpetrators (Bridges and McGrail 1989;Brown and Testa 2008;Gerdes et al 1988;Johnson and Jackson 1988;Maurer and Robinson 2008;Schneider et al 2009;Selby et al 1977;Workman and Freeburg 1999). Regarding perceptions of similarity, extant studies have demonstrated that perceivers who rate themselves more similar to sexual assault victims attribute less culpability to victims for their assaults (e.g., Amacker and Littleton 2010;Bell et al 1994;Dexter et al 1997;Feldman et al 1998;Grubb and Harrower 2008;Mason et al 2004;Workman and Freeburg 1999).…”
Section: Established Predictorsmentioning
confidence: 99%
“…There are a few studies that are exceptions to this, however, as they specify empirical linkages among perceiver variables. For example, regarding gender differences, research has shown that women more strongly identify with (i.e., view themselves more similar to; Deitz et al 1984;Maurer and Robinson 2008) and empathize with (Ching and Burke 1999;Deitz et al 1982) sexual assault victims, and men endorse greater rape myth acceptance (Johnson 1994;Johnson et al 1997;Kopper 1996;Millburn et al 2000;Payne et al 1999). Also, perceiver empathy has been found to be positively related to perceived similarity/identification with rape victims (Deitz et al 1982(Deitz et al , 1984Feldman et al 1998) and inversely related to rape myth acceptance (Gerger et al 2007).…”
Section: Established Predictorsmentioning
confidence: 99%
“…Subsequently, Workman and Orr (1996) and Workman and Freeburg (1999) used attribution theory to study the effects of sex of observer, rape myth acceptance, and victim dress on attributions of acquaintance rape and on attributions of responsibility and blame. Whereas other researchers manipulated many aspects of dress (e.g., Maurer and Robinson 2008;Whatley 2005) or did not explain what aspects were manipulated (Cassidy and Hurrell 1995) to convey provocativeness or sexiness of dress, Workman and Orr manipulated only one aspect of dress: skirt length. A model was photographed wearing a skirt that was 3 inches below the knee, was knee-length, or was three inches above the knee.…”
Section: Dress and Sexual Assaultmentioning
confidence: 99%